Differential Levels of Tl1a Affect the Expansion and Function of Regulatory T Cells in Modulating Murine Colitis. Issue 3 (March 2016) - Sidhu-Varma, Maninder; Shih, David Q.; Targan, Stephan R.
Abstract : Background: Expression of TL1A (tumor necrosis factor–like ligand 1A) is increased in patients with inflammatory bowel disease (IBD). Mice with elevated T-cell expression of Tl1a (L-Tg) have increased regulatory T cells, yet develop worsened colitis and intestinal fibrosis. The aim of this study was to investigate the role of Tl1a in the differentiation and function of Tregs and their effects in modulating murine colitis. Methods: Tl1a overexpressing L-Tg, Foxp3-mRFP (FIR)-LTg, and DR3KO-LTg mice were used for the study. In the L-Tg mice, Tl1a expressing cells can be identified by green fluorescent protein (GFP). Results: We report that Foxp3 expression in the L-Tg mice is variable based on high or low level of Tl1a expression, referred to herein as GFPhigh and GFPlow T cells. Treg-specific suppressive molecules were highly expressed on the GFPlow Foxp3 + Tregs and were significantly reduced on Tregs expressing high Tl1a. In vitro suppression function was significantly enhanced in the GFPlow compared with the GFPhigh Tregs. RAG −/− mice cotransferred with either GFPlow or wild-type Tregs were protected from colitis. Furthermore, GFPlow Tregs lost the suppression function in the absence of DR3 (Death receptor 3). Conclusions: Tregs expressing low levels of Tl1a ameliorate murine colitis and promote the maintenance of Treg suppressor function in a DR3-dependent manner, partly due to a heightened regulatory program. These data reveal novel roles for differential levels of Tl1a in regulating T cell–mediated immune responses that have implications in understanding the pathogenesis of IBD. Abstract : Article first published online 28 January 2016.